Influence of Motivation in The Formation of Discipline for Madrasah Ibtidaiyah Students - Rahmat Hidayat; Citra Eka Wulandari; Bella Dwi Regista Syukur (Universitas Muhammadiyah Ponorogo, 2021)
Discipline behavior is one of the most important behaviors to teach because it can make a person able to follow the rules. Schools are strategic environments for teaching disciplined behavior. The school education system requires students to be disciplined, and every student must always follow the existing rules. This study aims to provide insight into the factors that influence students in disciplinary behavior so as to facilitate an educational institution in improving discipline in the special education process at the Madrasah Ibtidaiyah level. This study uses a descriptive qualitative method through the approach initiated by Miles and Huberman. With data obtained by taking a survey on 163 students (male: 95; female: 68) from Madrasah Ibtidaiyah Nurussalam, Sambirejo, Mantingan, Ngawi, Indonesia. The results of the study indicate that there are several factors that influence the disciplinary behavior of madrasah ibtidaiyah students which are divided into four motivations, including: (1) internal motivation factor, this can be seen from the students' understanding of the discipline that has been applied in madrasah ibtidaiyah by being able to adapt to the school regulatory system, have good self-control (which is influenced by religiosity), and have high ideal motivation , and (2) external motivation factors, this can be seen from the support of parents, having responsibility and motivation to avoid punishment, and the influence of friends who have obeyed the rules.